Slotted Waveguide Circularly Polarized Leaky Wave Antenna With Improved Efficiency at W-Band - Shilpi Singh; Shakti Singh Chauhan; Ananjan Basu (IEEE Access, 2023)
This article presents a high-efficiency circularly polarized slotted waveguide leaky wave antenna for the W band frequency range. The wall thickness of the slotted waveguide leaky wave antenna containing the radiating slots is tuned to optimize the overall antenna performance. A thin dielectric layer with an array of metallic patches has been used as a linear-to-circular polarization converter. The fabrication challenges of the W band antenna have been overcome by CNC milling machines which provide a high degree of precision and accuracy. The gain of the prototype antenna is above 20 dBi in the intended operating band from 92 GHz to 98 GHz. Furthermore, the antenna provides an average half-power beamwidth (HPBW) of 3.2° in the elevation plane and a cross-polarization level below -18 dB in the main beam direction. The combination of its robust design, reliable fabrication, simple configuration, and superior performance makes the proposed antenna a strong candidate for various W band applications.